Phyllis of Scyros - Bonarelli, Guidubaldo, conte de', 1563-1608 (Italica Press dual-language poetry series, 2007)
"A dual-language (facing-pages) edition of 'Filli di Sciro, ' the Renaissance pastoral tragicomedy, with introduction, notes, selected bibliography "--Provided by publisher